2021
DOI: 10.5114/hpc.2021.110111
|View full text |Cite
|
Sign up to set email alerts
|

The life satisfaction of nurses during the covid-19 pandemic

Abstract: Authors' contributionWkład autorów: A. Study design/planning zaplanowanie badań B. Data collection/entry zebranie danych C. Data analysis/statistics dane -analiza i statystyki D. Data interpretation interpretacja danych E. Preparation of manuscript przygotowanie artykułu F. Literature analysis/search wyszukiwanie i analiza literatury G. Funds collection zebranie funduszy SummaryBackground. Life satisfaction is an overall assessment of an individual's satisfaction with life relative to personal standards. Peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In relation to the connection between life satisfaction and the psychological, social, and environmental domains of quality of life, our results coincide with the results of Yildrim and co-workers. Tomczyszyn et al [23] analyzed the life satisfaction of Polish nurses during the COVID-19 pandemic. They found that the majority of nurses reported a low to average level of life satisfaction.…”
Section: Raspravamentioning
confidence: 99%
“…In relation to the connection between life satisfaction and the psychological, social, and environmental domains of quality of life, our results coincide with the results of Yildrim and co-workers. Tomczyszyn et al [23] analyzed the life satisfaction of Polish nurses during the COVID-19 pandemic. They found that the majority of nurses reported a low to average level of life satisfaction.…”
Section: Raspravamentioning
confidence: 99%